The drawing of Architectural Rationalism in the Canary Islands: Miguel Martín Fernández de la Torre - Enrique Solana Suárez (Universitat Politècnica de València, 2021)
This paper presents the way of proceeding graphically, through architectural drawing, during the rationalist period in the Canary Islands. For this purpose, we have used a paradigmatic figure among the architects who developed their professional activity in the islands, his name is Miguel Martín Fernández de la Torre, who estudied architecture at the Madrid School of Architecture.